Aptikom Open Education Architectural Framework A Strategic Platform to Implement Online Learning in Higher Education Environment - Erick Dazki; Richardus Eko Indrajit - Institut Perbanas Jakarta (APMMI - Asosiasi Profesi Multimedia Indonesia, 2015)
Abstract - As the association of higher education institutions in computer science and information technology, APTIKOM has been appointed by the government of Indonesia to promote a massive implementation of open education system within the archipelago. Through a consortium of prominent colleges and universities, APTIKOM has introduced a framework of collaboration in open education ecosystem. Working together with the office of Indonesian Vice President and the Ministry of Education and Culture, APTIKOM launched a national program on promoting, educating, and socialising open education initiatives throughout the nation. In order to align this movement with several related initiatives in the past, a harmonisation and a synchronisation effort should be done. The open education movement in Indonesia can be divided into three domains: Open Content, Open CourseWare, and Open Campus. These three categories are being used as a foundation of understanding the open education movement within higher education environment. Together with PUSTEKKOM, the National Center of Information Technology for Education, APTIKOM is also developing an infrastructure architecture for implementing those open education domains. This article presents the open education architectural framework that is used as a common language among stakeholders in harmonising the initiatives nationwide and the infrastructure framework as the reference to develop the technology ecosystem.Keywords - Open Education, Open Content, Open CourseWare, Open Campus, Architecture, Framework